PENGARUH KAK SETO SEBAGAI CELEBRITY ENDORSER TERHADAP BRAND AWARENESS GRAB INDONESIA. (Survei Pada Followers Media Sosial Instagram @Grabid) - Hafiz Muhammad Rizky (2022)
This research was conducted to answer the problems that exist in the background of this research. This research aims to find out if there isi any influence Kak Seto as a Celebrity Endorser has on Grab Indonesia Brand Awareness on Instagram, and to find out how much influence Kak Seto has as a Celebrity Endorser on Grab Indonesia's Brand Awareness. The research method used is quantitative explanatory usi primary data sources from questionaires and secondary data from books, journals, and previous studies relevant to this research. Sampling technique is done by purposive sampling technique. In this study, the researcher carried out five stages of data analysis which is included data validity, reliability, correlation, coefficient of determination, and hypothesis testing.The final result of this study shows that there is a fairly high influence and relationship between Kak Seto as a celebrity endorser of Grab advertising on Grab Indonesia's brand awareness, where the result is obtained froma correlation test which shows a number of 0,759. In addition, there is a significant influence from Kak Seto's presence in Grab advertisements on brand awareness of Grab Indonesia where it is known that the influence caused bt Kak Seto is 65,2% obtained from the coefficient of determination test, while the remaining 34,8% isinfluenced by various other factors not examined in this study.